Study on the Inerting Effect and Migration Law of Nitrogen and Carbon Dioxide in Large Inclined Goaf by Physical Simulation Model - Xiaolin Song; Chunlei Wu; Chun Liu; Yanlong Li; Zhiyu Wang; Bobo Shi (Geofluids)
In this paper, the inerting effect and migration law of inert N2 and CO2 in large inclined goaf are studied using a physical simulation model. The differences in oxygen reduction and inert gas migration are analyzed and compared. The results show that as N2 and CO2 injection increased, the oxidation zone’s range and width shrunk, and the end of the loose and oxidation zones moved closer to the working face. The migration profile of CO2 and N2 resembled a trumpet and an L shape, respectively, and under the same inerting flow rate, the effect of CO2 inerting on oxygen reduction was much less significant than that of N2.